Video-assisted transcervical-transtracheal repair of posterior wall laceration of thoracic trachea: A new approach. Case Report - Tombelli, Simone; Viggiano, Domenico; Gatteschi, Lavinia; Voltolini, Luca; Gonfiotti, Alessandro (Frontiers in Surgery, 2023)
Iatrogenic tracheal lacerations are a rare but potentially fatal event. In selected acute cases, surgery plays a key role. Treatment can be conservative, for lacerations of less than 3 cm; surgical or endoscopic, depending on the size and location of the lesion and fan efficiency. There is no clear indication of the use of any of these approaches and the decision is therefore linked to local expertise. We present an emblematic clinical case of a 79 years old female patient undergoing polytrauma as a result of a road accident, without neurological damage, which required intubation and subsequent tracheotomy due to a significant limitation to ventilation. Imaging has shown the tracheal laceration involving the anterior wall and the pars membranacea up to the origin of the right main bronchus.A percutaneous tracheotomy was permormed without any improvement of the respiratory dynamic. Therefore, the patient underwent a surgical repair of the tracheal laceration with a hybrid mini-cervicotomic/endoscopic approach. This less invasive approach successfully repaired the extensive loss of substance.